Perceived Effectiveness of Students’ Punishment by Teachers in Osun State, Nigeria - Okesina, Falilat Anike; Famolu, Florence Bosede (Mimbar Sekolah Dasar, 2022)
Anti-social behaviors among Nigerian in-school adolescents continue to increase in an alarming rate. This study assessed teachers’ perceived effectiveness of punishment on student by in Osun State, Nigeria. Participants’ age and years of teaching experience were examined. The research design employed in this study was survey with a population of 200 teachers as the participants. For data collection, a questionnaire designed by the researcher was administered. Percentage, t-test and Analysis of Variance (ANOVA) were used to analyze the two postulated null hypotheses at 0.05 alpha level. Results showed that teachers in Osun State perceived punishment on students as highly effective; no statistical difference was found in the participants responses based on age and years of teaching experience. It was recommended that teachers should be aware of the positive ways of executing punishment for it to be effective by attending trainings, talk shows, seminars, and workshops.